2016
DOI: 10.1177/2211068216655524
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin in Treating Breast Cancer: A Review

Abstract: Breast cancer is among the most common malignant tumors. It is the second leading cause of cancer mortality among women in the United States. Curcumin, an active derivative from turmeric, has been reported to have anticancer and chemoprevention effects on breast cancer. Curcumin exerts its anticancer effect through a complicated molecular signaling network, involving proliferation, estrogen receptor (ER), and human epidermal growth factor receptor 2 (HER2) pathways. Experimental evidence has shown that curcumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
70
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 93 publications
(99 reference statements)
0
70
0
1
Order By: Relevance
“…1], isolated from the powdered rhizome of Curcuma longa L. (Zingiberaceae) (17,18), interacts with numerous biological targets, including inflammatory mediators, growth factors, enzymes, carrier proteins, metal ions, tumor suppressors, transcription factors, oncoproteins and cellular nucleic acids (19)(20)(21). Discovered in 1815 by Vogel and Pelletier as a yellow pigment (4), curcumin has been consumed for >2,000 years in Asian countries, due to its various medicinal properties against human diseases, including cancer and auto-immune diseases (10,17,(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…1], isolated from the powdered rhizome of Curcuma longa L. (Zingiberaceae) (17,18), interacts with numerous biological targets, including inflammatory mediators, growth factors, enzymes, carrier proteins, metal ions, tumor suppressors, transcription factors, oncoproteins and cellular nucleic acids (19)(20)(21). Discovered in 1815 by Vogel and Pelletier as a yellow pigment (4), curcumin has been consumed for >2,000 years in Asian countries, due to its various medicinal properties against human diseases, including cancer and auto-immune diseases (10,17,(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, natural products have formed an important part of drug discovery. Among these natural products, curcumin (diferuloylmethane), a hydrophobic polyphenol derived from turmeric (Curcuma longa) has been used for the treatment of numerous diseases, including cancer (9). Curcumin possesses several beneficial properties, including anti-inflammatory, anti-metastatic and anti-carcinogenic effects, as well as acting as an inhibitor of tumor formation (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have indicated that curcumin is able to inhibit proliferation and survival, induce apoptotic and non-apoptotic (autophagocytosis and paraptosis) cell death, and reduce invasion and migration in various types of malignant cancer cells (7)(8)(9). Through regulation of the expression of genes associated with programmed cell death, curcumin causes a high degree of apoptosis in human breast cancer cells (10). However, few studies have been performed that investigate the underlying mechanisms of curcumin as a potential agent in breast cancer therapy.…”
Section: Introductionmentioning
confidence: 99%